Comparison of Levels and Types of Aggressive Behaviours among Students of Islamic Secondary Schools in Terengganu - Mohd Nor, Noraniza; Mohamad Syed Abdullah, Syed; Nur Hadis A Rahman, Siti; Marzuki Mohamad, Ahmad; Talhah Ajmain @ Jima’ain, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The increase in levels of aggressive behaviour involving bullying, hitting, and injuring others amongst students has reached the level of concern in today’s society. This study aimed to measure the level of students’ aggressive behaviour involving four types of aggression: physical aggression, verbal aggression, anger aggression, and hostility aggression. The data used to measure these types of aggression was gathered by the Aggression Questionnaire by Buss & Perry (1992). This study was focused on students (n = 200) of several Islamic secondary schools in Terengganu. The methodology of this study was using quantitative studies by distributing questionnaires and analysing them using Statistical Package for Social Science (SPSS) version 23.0. The findings of this study showed that the levels of physical aggression (2.4467), verbal aggression (2.9071), anger aggression (2.6571), and hostility aggression (3.1736) were at a moderate level. The findings of this study also found that there was no significant difference between physical aggression and verbal aggression based on gender, but there was a significant difference between anger aggression and hostility aggression among female and male students of Islamic secondary schools. Therefore, it is recommended that aggressive behaviour of students of Islamic secondary schools be taken into consideration by educational institutions as well as those who plan intervention programs for students.